Study on the Relationship between Early Shrinkage Cracking and Mechanical Properties of Nano-Clay Cement Mortar Based on Fractal Theory - Shiyi Zhang; Zhisheng Fang; Wenjie Qi; Yingfang Fan; Surendra P. Shah (Buildings, 2023)
In order to study the influence of nano-clay on the crack resistance of cement-based materials, two kinds of nano-metakaolin (NMK) and two kinds of nano-attapulgite clay (NMA) were considered. The early cracking process and mechanical properties of nano-clay cement mortar (NCM) was studied by using a plate knife-edge constraint test. Based on fractal theory, the distribution characteristics of NCM surface cracks were revealed, and the calculation method forNCM maximum crack width was given. The results show that the cracking time of the NMK-3 specimen is 2 and 6 h later than that of NMK-1 and NMA-2, respectively; the smaller the particle size of nano-clay, the earlier the cracking time of the specimen. However, nano-clay effectively inhibited the expansion of mortar cracks, and the cracks on the surface of NCM were thin and sparse. At 28 days, the maximum crack width of NMK-3 was 46.7% and 33.3% lower than that of NMK-1 and NMA-2, respectively. NMK hadthe best improvement effect on the mechanical properties cement mortar. The smaller the particle size, the more pronounced the improvement effect.The flexural strength ratio and compressive strength ratio at 7 and 28 days are 76.7%, 67.4%, and 61.2%, respectively.The distribution of surface cracks on NCM has fractal characteristics, and the fractal dimension of surface cracks is smaller than that of ordinary cement mortar. The larger the particle size of nano-clay, the smaller the fractal dimension of cracks. The quantitative relationship between fracture fractal dimension and NCM elastic modulus and shrinkage tensile stress is established.